Differentiation of globular phytoliths in Arecaceae and other monocotyledons: morphological description for paleobotanical application - Benvenuto, María Laura (2015)
Globular phytoliths have been mainly assigned to palms, woody trees, and other monocotyledon families from tropical regions. The lack of detailed descriptions of this phytolith morphology and its correct assignments to particular groups could lead to erroneous interpretations of phytolith records. In order to improve paleobotanical interpretations of phytoliths records, we analyzed the phytolith content and described the quantitative and qualitative characters of globular phytoliths of Arecaceae, Bromeliaceae, Cannaceae, Marantaceae, Orchidaceae, Strelitziaceae, and Zingiberaceae species from Argentina. Phytoliths were extracted by calcination and multivariate analyses were used to analyze their taxonomic relevance. Phytolith assemblages allowed the differentiation 1) among Zingiberales species; 2) among Arecaceae species; 3) between Orchidaceae, Arecaceae, and Bromeliaceae families; and 4) between Zingiberales and the rest of the groups. The study of distinguishing features of globular morphologies (such as size, roundness, reniformity, number of spines, spine length, and density of spines) allowed the discrimination between two Arecaceae subfamilies, and among Bromeliaceae, Cannaceae, and Zingiberaceae families. This work showed the importance of both analyses (phytolith assemblages and phytolith morphometric) in the identification of groups at different levels and represented the first detailed and comparative description of globular phytoliths of palms and other monocotyledons from Argentina.